MORPHOMETRIC CHANGES OF BUCCAL EPITHELIOCYTES AND ERYTHROCYTES IN STUDENTS WITH VARIOUS LEVEL OF SOMATIC HEALTH AND GENERAL PHYSICAL HARDINESS - Gavrilova, N.V.; Yatciv, Ya.N.; Lapkovskyi, E.I.; Popel, S.L.; Synitsa, A.V.; Mochernyuk, V.B. (World of Medicine and Biology, 2018)
The aim of the research was to study the morphometric changes in buccal epitheliocytes of students with different levels of somatic health and their correlation with the duration and quality of performance of the 12 min shuttle race with an acceleration of the run time of 20 m of segments. Indicative of the importance of morphometric examination of buccal epitheliocytes and erythrocytes of peripheral blood, as active participants in maintaining homeostasis and local factors of resistance of the body. Students with different levels of somatic health experience regular changes in the morphometric parameters of buccal epitheliocytes and erythrocytes of peripheral blood before and after testing the body's overall physical endurance. At the same time, the share of discocytes decreased dynamically and the content of spherocytes and stomatocytes increased. The results of the study show that when the maximum physical load is performed, the microrelief is significantly enriched and the peripheral blood erythrocytes are deformed, which indicates the low stability of their membranes to the effect of various stress factors at a low level of somatic health of the students. Different correlation between the obtained morphometric indices was demonstrated, and a direct correlation between the nuclear-cellsic ratio and the achieved level of shuttle run was revealed.
Keywords: epitheliocyte; erythrocyte; morphometry; nuclear-cellsic ratio; somatic health; general hardiness